2011
DOI: 10.4155/bio.11.156
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to Reduce Interference Due to In-Source Collision-Induced Dissociation of Acylglucuronides in LC–MS/MS

Abstract: We have shown that monitoring the parent drug [M-H](-) or [M+NH(4)](+) whenever possible could be an easy approach used by bioanalytical scientists to minimize the impact of in-source CID of acylglucuronides to the parent drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…As presented earlier in this manuscript, in-source dissociation of tacrolimus-glucuronide was a cause of concern during method development. Such a phenomenon has already been described for other directly conjugated drugs [22,23]. In the first steps of the method development, a duplication in patients' tacrolimus chromatographic peaks appeared.…”
Section: Discussionmentioning
confidence: 64%
“…As presented earlier in this manuscript, in-source dissociation of tacrolimus-glucuronide was a cause of concern during method development. Such a phenomenon has already been described for other directly conjugated drugs [22,23]. In the first steps of the method development, a duplication in patients' tacrolimus chromatographic peaks appeared.…”
Section: Discussionmentioning
confidence: 64%
“…SUM and its internal standard, NARA have been studied previously in positive ionization mode as they have secondary amino groups which can be readily protonated [56]. Although, NAP and INDO can be easily ionized in the negative ionization mode due to the presence of carboxylic acid group, it was observed that both were readily ionized in the negative as well positive ionization modes [57]. Moreover, the peak intensities were comparable in both the modes and hence all four analytes were ionized under positive ionization mode without polarity switch.…”
Section: Methods Developmentmentioning
confidence: 96%
“…Two mass transitions for the analyte may be included in the acquisition method, which will provide an alternative if matrix effects or interference is observed in one transition. For a carboxylic acid containing drug, monitoring acyl glucuronide metabolite in addition of the parent compound helps to identify potential erroneous results [9,[11][12]. To minimize carry-over, the injection sequence should be arranged so that the samples with the same time points are injected together and samples with a lower expected concentration should be injected before those with a higher expected concentration.…”
Section: Data Acquisitionmentioning
confidence: 98%